Makna Pesan Moral pada Konten Youtube RJL 5 Fajar Aditya dalam Episode “Tersesat 3 Hari di Gunung Slamet” (Analisis Semiotika Roland Barthes) - Sulistiawan, Handri; Hardian, Arvin; Ekowati, Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to identify and analyze the meaning of moral messages in RJL 5 YouTube content by Fajar Aditya, especially in the episode “Lost 3 Days on Mount Slamet”. In the digital era, media such as YouTube plays an important role in conveying educational and entertainment values. This episode attracts attention because it tells a true story with deep moral messages, such as the importance of preparation before climbing, awareness of safety, teamwork, and mental toughness in emergency situations. The research used a semiotic analysis method with a qualitative approach and data collection techniques of direct observation of the selected video content, supported by Roland Barthes' semiotic theory and moral communication theory to reveal the meaning of the narrative and visuals. The results show that this episode contains strong moral messages about the importance of permission from parents when going on a trip, preparation in climbing, patience, and mental resilience in dealing with extreme situations such as getting lost in the wild. This content is not only entertaining but also provides valuable learning, and is expected to encourage creators to pay attention to moral and educational aspects in the works presented. This research also contributes to communication studies in understanding the role of digital media as a means of conveying moral values.